2013
DOI: 10.1016/j.mgene.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence in natural populations of bronze featherback, Notopterus notopterus (Osteoglossiformes: Notopteridae) from five Indian rivers, analyzed through mtDNA ATPase6/8 regions

Abstract: The present study characterized 842 bp fragment of mitochondrial ATP synthase 6 and 8 (ATPase6/8) genes in Notopterus notopterus. In all, 97 samples of N. notopterus were collected from five distant rivers; viz Satluj, Gomti, Yamuna, Brahmaputra and Mahanadi representing 4 river basins in India. The analysis of variation revealed presence of 23 haplotypes in ATPase6/8 gene with haplotype diversity (Hd) of 0.899 and nucleotide diversity (π) of 0.00336. The within population variation which was 41.78% of the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Mitochondrial ATPase 6/8 genes are generally variable in vertebrates and have also been used in population studies (Zardoya et al, 1996). They were successfully used in genetic structure analyses in fishes of Indian waters such as Channa marulius (Habib et al, 2012); Notopterus notopterus (Gupta et al, 2013); Labeo rohita (Rupesh et al, 2014); Pampus argenteus (Divya et al, 2015); Coilia dussumieri (Kathirvelpandian et al, 2014). No published information is yet available on the population structure analysis of R. canadum along the Indian waters.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial ATPase 6/8 genes are generally variable in vertebrates and have also been used in population studies (Zardoya et al, 1996). They were successfully used in genetic structure analyses in fishes of Indian waters such as Channa marulius (Habib et al, 2012); Notopterus notopterus (Gupta et al, 2013); Labeo rohita (Rupesh et al, 2014); Pampus argenteus (Divya et al, 2015); Coilia dussumieri (Kathirvelpandian et al, 2014). No published information is yet available on the population structure analysis of R. canadum along the Indian waters.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that this species reaches up to 60 cm in standard length (Roberts 1992). A wealth of data is available for this species, documenting its reproductive behaviour and embryonic development (Yanwirsal et al 2017), cytogenetics (Barby et al 2019) and phylogeography (Gupta et al 2013;Takagi et al 2010). However, none of these studies simultaneously examined specimens sampled across the whole distributional range of N. notopterus.…”
Section: Introductionmentioning
confidence: 99%